Seborrheic keratosis of the nasal tip-an unusual case report (Bangladesh Journal of Otorhinolaryngology, 2016)
Seborrheic keratosis is a benign tumour of skin, a common hyperkeratotic lesion of the epidermis,that usually occurs in the trunk and less frequently in the extremities, face and the scalp. A 65-year old farmer presented with a long standing, slowly growing, firm, redbrown, polypoidal mass about 2×2.5 cm in size, located at the skin mucosa interfare of the tip of nose. The lesion was excised under general anesthesia and histopathologic examination showed seborrheic keratosis. Diagnosis is made on the basis of clinical & histopathological examination. Here, we discuss the clinical presentation, differential diagnosis, pathological diagnosis and management of such a case. There was no recurrence during a year follow-up.Bangladesh J Otorhinolaryngol; October 2015; 21(2): 119-121